1978
DOI: 10.1093/ajcn/31.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in chronic undernutrition

Abstract: Anthropometric (height, weight, and skinfolds), biochemical (serum proteins, albumin, and cholesterol), metabolic (nitrogen balance and creatinine excretion), hematological (plasma volume, hemoglobin, hematocrit, bone marrow hemosiderin, percent transferrin saturation, vitamin B12, and folic acid) variables and body water compartments (total and extracellular) have been measured in 49 adult male subjects who exhibited a wide range of nutritional states from normal to severely undernourished. Changes in body co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 37 publications
6
56
0
Order By: Relevance
“…It shows that the more severe the malnutrition, the larger the extracellular water inflation and the intracellular water depletion. In this study (Barac-Nieto et al, 1978), nitrogen balance can be shown to be inversely correlated to the degree of cellular dehydration (as assessed from the ratio of intracellular water over fat-free mass). However, nitrogen balances were very close to zero, probably reflecting that chronic malnutrition results in adaptation of protein metabolism to limit proteolysis.…”
Section: Changes In Water Compartments In Diseased Humansmentioning
confidence: 73%
See 2 more Smart Citations
“…It shows that the more severe the malnutrition, the larger the extracellular water inflation and the intracellular water depletion. In this study (Barac-Nieto et al, 1978), nitrogen balance can be shown to be inversely correlated to the degree of cellular dehydration (as assessed from the ratio of intracellular water over fat-free mass). However, nitrogen balances were very close to zero, probably reflecting that chronic malnutrition results in adaptation of protein metabolism to limit proteolysis.…”
Section: Changes In Water Compartments In Diseased Humansmentioning
confidence: 73%
“…There are few studies challenging this theory at the whole-body level. It appears that protein metabolism is probably regulated by Data are taken from the work of Barac-Nieto et al (1978). cellular hydration in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were classified into 2 groups: patients with an absolute BCM in the lowest quartile of values among patients of the same sex and patients in the lowest quartile of values among patients of the same sex. Absolute cutoff points of BCM normalized for height reported previously 23,24 for healthy and malnourished patients were not used because method and temporal differences between these earlier reports and our current study made direct comparisons potentially invalid. Data are presented as means Ϯ SD.…”
Section: Discussionmentioning
confidence: 97%
“…Normalization of BCM for height is necessary because absolute values of BCM vary widely with body habitus. 23,24 Reference to a physical characteristic provides a more definitive index of BCM. Height is considered a better index for normalization than weight because height is not affected by fluid retention (ascites) or malnutrition.…”
Section: Methodsmentioning
confidence: 99%